Impact of Asia-Pacific Economic Cooperation (APEC) to the contemporary economy - Agnieszka Drews (Institute of Economic Research (IER), 2015)
Trade is one of the important aspects of economic policy in the contexts of the third wave of regionalism. It is proven by growing number of trading agreement between regions and what goes after, expansion of positive aspects of economic cooperation. The aim of this article is to describe liberalization of trade and its changes through the ages and also deep analysis of influence of APEC at world economy. In this document the secondary data analysis and review of available literature was used. Analysis let claim that regional integration groups, with APEC in between, have crucial influence at trade and foreign direct investment creation.
Keywords: J51; F13; F42; N75; O11; O24; 330; interregional trade agreements; trade liberalization; regionalism; APEC